Proximity to Alcohol Sellers and Dose Response Relationship Between Alcohol Consumption With Intimate Partner Violence in Rural Southwestern Uganda - Ohurira, Tushaba (Journal of interpersonal violence, 2023)
Introduction: Intimate partner violence (IPV) is associated with several adverse public health outcomes and alcohol use is one of its risk factors. Proximity to alcohol selling points could be linked with problem drinking and IPV. We aimed to determine whether proximal location to alcohol and intensity of alcohol consumption are associated with IPV in rural southwest Uganda.Methods: We conducted a cross-sectional study in rural southwest Uganda with structured interviews at household level. We used the alcohol use disorders identification test (AUDIT) and the Conflict Tactics Scale to measure past year alcohol consumption and IPV (perpetration and victimization). We estimated Euclidean distances between participants’ households and nearest alcohol outlets using geographic information systems. We used generalized estimating equation models to calculate adjusted odds ratios (aOR) for the factors associated with IPV.Results: We enrolled 742 participants and median age was 41 years (inter-quartile range or IQR 32-53) and 52.2% of respondents were male. The overall prevalence of IPV in the past year was 52.2%. In a multivariable regression model, women (aOR = 2.24, 95%CI 1.28, 3.91) compared to men, those living proximal to an alcohol selling point (OR = 1.77, 95% CI 1.38, 2.27) were more likely to experience IPV. There was a dose-response relationship between alcohol consumption and IPV. With non-drinkers as the reference category, the aORs were 4.54 (95% CI 2.04, 10.08) for casual drinkers, 10.53 (95% CI 4.15, 26.77) for hazardous drinkers and 15.31 (95% CI 4.73, 49.54) for alcohol dependent drinkers.Conclusion: IPV is very common and has a dose-response relationship with alcohol consumption and drinking outlet proximity. There is an urgent need for IPV and alcohol interventions programs in these rural communities. Policy to restrict proximity of alcohol outlets to residential locations should be examined as an intervention for alcohol consumption and IPV perpetration.